HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR PADA SISWA KELAS V SEKOLAH DASAR - Ijrah, Sumarnur; Abidin, Zainal; Lubis, Mansur (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
Following research is purposed to find out if there is a relationship between Learning Motivation and study's result on fifth grade of national elementary school number four subdistrict Banuhampu, Agam regency. Population in this research are 159 students with 61 students as sample. Data is analyzed by using Pearson Correlation shows that there is relationship 0,936 and r table df=59 with 5% significance 0,2521, which means counted r is bigger than r table (0,936>0,2521), and obtained significance 0,000 which is smaller than 0,05. this result shows that there is a significance relationship between Learning Motivation and Study's result on fifth grade of  national elementary school number four subdistrict Banuhampu, Agam regency. Keywords : Learning Motivaton, Study's Result